Biocontrol of rhizome rot of ginger using selected aqntagonists - Julie George K (Department of Plant Pathology, College of Horticulture, 1999)
Rhizome rot of ginger cas used by Pythium aphantdermatum (Edson) Fitzpatrick is one of the most destructive diseases of ginger in Kerala. The pathogen was isolated and its pathogenecity was established by Koch's postulates in ginger variety Rio-de-Jenerio. Among the various food bases evaluated, for the mass multiplication of selected antagonists, rice hull was found to be significantly superior to all others to obtain maximum growth for Trichoderma viride and Aspergillus flavus. For Aspergillus niger, rice bran was found to be significantly superior. The results on the effect of various treatments on germination showed that there was no significant difference among the treatments. The effect of antagonists on the pre- emergence rotting and post-emergence rotting (rhizome rot) were studied. In plots where antagonists (T viride, Aflavus or A. niger) or fungicides (mancozeb or copper oxychloride) were applied either as seed treatment or as soil incorporation at the time of planting, the pre-emergence rotting was not observed. The plot in which the antagonists T. vtride, A. mger and At flavus were applied in combination at 60 and 120 OAP, recorded the minimum rhizome rot incidence compared to other treatments. The plots in which the antagonists were applied twice, i.e., 60 and 120 OAP, the rhizome rot incidence was minimum compared to the plots with only one time application of antagonists. The maximum population of the pathogen P. aphanidermatum. was observed in plot where A. flavus was applied in combination with mancozeb. The multiplication of selected antagonists, 7: viride, A. flavus and A. niger in soil was found out by estimating their population at different stages. The population of T. virtde was maximum in plots where it was applied in combination with mancozeb in most of the period. The soil application of the combination of antagonists T. viride, A. flavus and A. niger did not affect the multiplication of anyone of them in soil. In general, soil incorporation of antagonists was found to helping in their mulitplication profusely compared to the seed treatment. The incorporation of the antagonists A. flavus and A. niger to the plots, twice was found to be superior than applying them only once, for getting maximum multiplication of propagules in soil. The result on the compatibility of antagonist with fungicide in field condition revealed that the antagonist T viride was quite compatible with mancozeb whereas A. flavus and A. niger were compatible with